Unleashing Animal Spirits - Self-Control and Overpricing in Experimental Asset Markets - Martin Kocher; Konstantin Lucks; David Schindler (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
One explanation for overpricing on asset markets is a lack of tradersśelf-control. Self-control is the individual capacity to override or inhibit undesired impulses that may drive prices. We implement the first experiment to address the causal relationship between self-control abilities and systematic overpricing on financial markets. Our setup can detect some of the channels through which individual self-control restrictions could transmit into irrational exuberance in markets. Our data indicate a large direct effect of restricted self-control abilities on market overpricing. Low self-control traders report stronger emotions after the market.
Keywords: G02; G11; G12; D53; D84; 330; behavioral finance; trader behavior; self-control; experimental asset markets; overpricing